Evaluation of Students’ Learning Outcomes in the Implementation of the Accounting Curriculum in Secondary Schools in Rivers State - Innocent, Richard; Bupo, Godwin Omoni; Wogboroma, Nyemaekile (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The study investigated the evaluation of students’ learning outcomes in the implementation of the accounting curriculum in secondary schools. Specifically, the study focused on how contextual factors influence curriculum implementation and the extent to which students achieve the set objectives of the accounting curriculum. Two research questions guided the study, and one hypothesis was tested at the 0.05 level of significance. The study adopted an evaluation survey research design. The population comprised 367 accounting teachers and 177,369 accounting students. A stratified random sampling method was used to select a total sample of 583 respondents, including 184 teachers and 399 students. Data were collected using a researcher-developed questionnaire titled "Evaluation of Students’ Learning Outcomes in the Implementation of the Accounting Curriculum in Secondary Schools Questionnaire (ESLOIACSSRSQ)", consisting of 20 items across two sections. The instrument was validated by three experts in Business Education and Measurement and Evaluation, and its reliability was confirmed using the Cronbach’s Alpha method, yielding coefficients of 0.89. A total of 567 valid responses were retrieved and analysed. Descriptive statistics (mean and standard deviation) were used to answer the research questions, while regression analysis was used to test the hypothesis. The findings revealed that contextual factors, including support from parents, industries, government, and corporate groups, positively influenced curriculum implementation. While contributions from religious bodies and individuals were minimal, the overall level of contextual involvement was high. The study also showed that students largely met the curriculum objectives, demonstrating competence in key areas such as financial reporting and bookkeeping. Regression analysis confirmed that contextual factors made a significant contribution to the successful implementation of the accounting curriculum. Based on the findings, the study recommends that schools strengthen links with industries for practical learning opportunities and invest in digital accounting tools to improve students' technological competence in accounting.